How did Tokopedia assist economic recovery through the MSMEs during the Covid-19 pandemic? - Inas Nurfadia Futri; Fifi Afisah; Nugroho Saputro (Universitas Sebelas Maret, 2021)
Discussing business during the Covid-19 pandemic is very interesting, especially about the acceleration of digitalization transformation in the country. Indonesia is predicted to have a high potential for digital economic growth in Southeast Asia. Online retail stores or e-commerce are part of the digital economy ecosystem growing rapidly in Indonesia. Tokopedia is an e-commerce technology company from Indonesia that has a mission to equalize the digital economy. This mission is in line with the Indonesian government, seeking to accelerate digital transformation, especially for local MSMEs (Micro, Small, and Medium Enterprises) as one of the drivers of the economy, especially during the Covid-19 pandemic. With the dominance of sellers from local MSMEs, Tokopedia contributes to the movement of the economy in Indonesia. Therefore, in addition to discussing the e-commerce digital economy ecosystem in Indonesia, this article aims to discuss Tokopedia's strategies in helping Indonesia's economic recovery during the Covid-19 pandemic through the digitalization of MSMEs. Tokopedia's series of strategies to digitize MSMEs provide inspirational stories to always be active in developing creative and innovative ideas in business processes.